PERAN WTO DALAM PENYELESAIAN SENGKETA PERDAGANGAN INTERNASIONAL - Agnes E Manalu; Anastasya Sembiring, Debora Matanari, Putriana Sinaga, Yakinda Munthe (ADISAM PUBLISHER, 2025)
The World Trade Organization (WTO) is an international organization that plays an important role in regulating trade between countries with the aim of creating transparency and openness in global trade. Established on January 1, 1995, replacing GATT, the WTO was born from the Uruguay Round agreement and has regulations that must be obeyed by all member countries, especially regarding international trade discipline. The WTO provides a structured dispute resolution mechanism, including consultation, panel formation, and appeal review, to resolve conflicts arising from violations of trade agreements. One example is the case of violations of Indonesian nickel ore exports and the European Union's anti-dumping policy. This study highlights the strategic role of the WTO in preventing retaliatory actions, maintaining global economic stability, and ensuring fairness and effectiveness in resolving international trade disputes. These findings are relevant for International Relations students in understanding the role and challenges of the WTO system as an important element in the global trade architecture